Strengthening Family and Community Roles in Elderly Rehabilitation for Osteoarthritis Prevention - Aisyah, Aisyah; Pane, Rita Vivera; Ambarsari, Utami; Alfan, Moh Nabil; Abidin, Rully Genadi; Wijaya, Annisa' Dharmestha; Ramadhana, Ain Darojah Siddiq (UKInstitute, 2026)
The elderly population in Surabaya exceeds 350,000 individuals, presenting major challenges in musculoskeletal health, particularly osteoarthritis, which contributes to pain, functional limitations, and reduced independence. A preliminary community survey in Wonocolo District showed that 35.7% of older adults experienced knee pain, particularly during stair climbing, squatting, and sit-to-stand movements, indicating an urgent need for preventive and functional rehabilitation strategies. Families and community health cadres hold a key role, yet their knowledge and skills in assisting elderly mobility and joint-protection activities remain limited. This community engagement program aimed to strengthen family and cadre capacity in elderly rehabilitation and osteoarthritis prevention through structured education, functional exercise training, and health literacy improvement. The intervention was conducted from February to July 2025 and involved 40 elderly participants and 32 family caregivers and health cadres. Activities included community health education, hands-on functional exercise training, mobility modification for prayer movements, screening for common comorbidities, and pre- and post-test knowledge assessments. Qualitative feedback was obtained to evaluate perceived benefits and readiness for sustainability. Participants demonstrated significant improvement in knowledge, with post-test scores showing more than 85% achieving 8–10 correct answers compared to pre-program scores of 4–6. Elderly participants reported decreased stiffness, increased mobility confidence, and improved ability in daily movements such as sit-to-stand transitions. Families and cadres exhibited enhanced skills in supervising exercises and assisting safe transfers. Screening activities also identified undiagnosed hypertension, hyperglycemia, and hyperuricemia, which were referred to primary health care services. The program effectively enhanced health literacy, mobility skills, and caregiver involvement in elderly rehabilitation. Strengthened family and cadre participation supports program continuity and sustainable community-based healthy aging initiatives. Future programs should include periodic follow-up training, integration with primary health services, and expansion of digital education resources to reinforce long-term behavior change.